(untitled) (Colombia Medica, 2017)
Background:Adult T-cell Leukemia/Lymphoma (ATLL) is classified as a peripheral CD4+ T-cell neoplasm caused by the human T-cell lymphotropic virus type 1 (HTLV-1). Typical symptoms are associated with leukemic infiltration; however, atypical and exaggerated manifestations of verrucous carcinoma have also been described. Case report:We present here the case of a patient with multiple skin lesions, ischemic necrosis in the hallux and lymphadenopathies. Biopsies were taken, which showed verrucous epidermal carcinoma and cutaneous lymphoma. Splenomegaly and adenopathy in mesentery, retro peritoneum and lymph node chains in the limbs were observed. Bone marrow examination showed findings compatible with T-cell leukemia/lymphoma; and it was ELISA positive for HTLV-1/2. Treatment and outcome:The patient had a good initial response to a CHOP scheme (cyclophosphamide, doxorubicin, vincristine and prednisone) with filgrastim. However, the patient had a relapse and died before the second cycle. Clinical relevance:Comorbidity could lead to the associated risk factors model. According to this model, secondary immunodeficiency caused by HTLV-1 may induce the development of verrucous carcinomas; alternatively, the disease could be due to a correlation between HTLV-1 and the human papillomavirus (HPV).